PENGARUH DUKUNGAN ORANG TUA, MOTIVASI DAN KESEMPATAN KERJA TERHADAP KEPUTUSAN MEMILIH PROGRAM STUDI DENGAN MINAT SEBAGAI VARIABEL INTERVENING - Hayati, Sri; Lestari, Kurnia Fitri; Maesaroh, Siti; Setijadi, Setijadi (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
ABSTRACT The high number of students who choose the Management study program at STIE Tamansiswa Banjarnegara causes a fairly high difference between the number of students in the Management and Accounting study program. This study aims to determine the effect of parental support, motivation and job opportunities on the decision to choose a study program with interest as an intervening variable. This study uses quantitative methods using a sample of 87 respondents from STIE Tamansiswa Banjarnegara students. This study used a questionnaire with a Likert scale as a data collection tool. The analytical technique used is instrument test, classical assumption test, path analysis and Sobel test. The results of this study indicate that motivation and interest partially have a significant influence on the decision to choose a study program. Parental support and job opportunities partially have no significant influence on the decision to choose a study program. Parental support, motivation and job opportunities partially have a significant effect on the interest of the study program. Based on the results of the Sobel test, interest can mediate the effect of parental support on the decision to choose a study program, interest can mediate the influence of motivation on the decision to choose a study program and interest can mediate the effect of job opportunities on the decision to choose a study program. The magnitude of the coefficient of determination (R Square) in the first equation is 0,720 which means that 72% of the interest variable is influenced by the variables of parental support, motivation and job opportunities, while the second equation shows an R Square value of 0,552 which mean that 55,2% of the decision variables to choose are influenced by the variables of parental support, motivation, job opportunities and interest.